Effect of Ion Exchanged to the CO2 Adsorption on MFI Zeolites - Wirawan, Sang Kompiang; Warmanda, I Wayan; Wahyuni, Endang Tri (ASEAN Journal of Chemical Engineering, 2013)
The adsorption of CO2 on MFI (HZSM-5) and ion exchanged MFI (CaZSM-5) zeolites were studied by a temperature programmed desorption (TPD). The adsorption measurements were conducted at temperatures from 323 to 473 K at atmospheric pressure. The results showed that CO2 was adsorbed on HZSM-5 by one type of adsorption, and on CaZSM-5 zeolites by at least two types of adsorption over the temperature range studied. One was a weak adsorption probably due to interaction with the framework of ZSM-5, and the other was a stronger adsorption caused by interactions with the Ca cations of ZSM-5. The adsorption behavior for HZSM-5 was described by a single site Langmuir adsorption model but for CaZSM-5 a dual site Langmuir model was used. The TPD results indicated that the quantity of irreversibly adsorbed CO2 on HZSM-5 was undetectable.